Zagadnienie przeniesienia sędziego na inne miejsce służbowe - Kessler, Marta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The article deals with the transfer of common court judge to other place of judiciary at his request, the nature of the legal relationship of the administrative judges of the courts of law for examining applications, procedures for handling requests for the transfer of judges
Keywords: universal court judge; moving the judge; ndependence of the judiciary; independent and impartial judiciary; authority administrative